Ação, ordem e cultura: fundamentos de um programa de pesquisa weberiano - Schluchter, Wolfgang (Politica & sociedade, 2020)
More than interpreting, it is necessary to develop Max Weber. Based on this premise, the article situates the current state of the current theoretical discussion in sociology and presents ten key points for the construction of a Weber paradigm or a Weberian research program.
Gesehen am 16.11.2021